ASSESSING THE SATISFACTION LEVEL OF RURAL TOURIST HOUSEHOLDS (RTH) IN SERBIA WITH THE ECONOMIC SUSTAINABILITY DIMENSION - Katica Radosavljević; Vesna Paraušić; Branko Mihailović; Danijela Pantović (Ekonomika Poljoprivrede (1979))
The aim of the research is to examine the economic efficiency of rural tourist households in the Republic of Serbia engaged in rural tourism at their households. To achieve the research goal, two dependent variables were observed: (1) satisfaction with tourist visits and accommodation capacity occupancy, and (2) satisfaction with earnings from rural tourism and the possibility of investment return in this activity. The non parametric Kruskal–Wallis test was employed to examine differences between groups. The research revealed no statistically significant difference in the level of satisfaction with tourist visits and capacity occupancy among respondents with different demographic, socio-economic, and business characteristics. Regarding satisfaction with income from rural tourism and the possibility of investment return in rural tourism among respondent groups, the application of the Kruskal–Wallis test detected differences only based on the Age of the respondents and Dominant sources of income in the rural tourist household.